2021
DOI: 10.1021/acsanm.1c00569
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Terbium-Based Nanorods as Multimodal Bioimaging Contrast Agents

Abstract: Diagnostic imaging strongly relies on the use of contrast agents (CAs). In general terms, current CAs present undesirable side effects that encourage researchers and pharmaceutical companies to continually search for safer and more versatile alternatives. Here, we describe the synthesis and characterization of terbium-based nanorods (TbNRs) as a potential alternative to traditional CAs for magnetic resonance imaging (MRI) and X-ray computed tomography (CT). The paramagnetism and high atomic number of Tb provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…However, D-glucuronic acid with a smaller size than PAA can allow more water molecules to closely approach the NP, making more water molecules feel stronger magnetic fields (B) generated by the NP, consequently making the D-glucuronic acid-coated NPs have a higher r 2 value. On the other hand, large NPs and nanorods [53,54] exhibited high r 2 values even with a large ligand coating because of their enhanced paramagnetic magnetic moment per NP or per nanorod, which increases with increasing particle size and because the r 2 value is proportional to the square of the magnetic moment [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, D-glucuronic acid with a smaller size than PAA can allow more water molecules to closely approach the NP, making more water molecules feel stronger magnetic fields (B) generated by the NP, consequently making the D-glucuronic acid-coated NPs have a higher r 2 value. On the other hand, large NPs and nanorods [53,54] exhibited high r 2 values even with a large ligand coating because of their enhanced paramagnetic magnetic moment per NP or per nanorod, which increases with increasing particle size and because the r 2 value is proportional to the square of the magnetic moment [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, very few significant studies indicate the potential toxicity of TbNPs in biological systems. In the dynamic realm of biomedical research, TbNPs have emerged as promising contenders for a plethora of applications, ranging from targeted drug delivery to advanced imaging modalities. , However, as we navigate the exciting potential of TbNPs in the biomedical landscape, it becomes imperative to scrutinize and understand the subtle toxicological concerns that may accompany their integration into biological systems. , Drawing from the convergence of nanotechnology and medicine, we delve into the multifaceted interactions between TbNPs and biological entities, focusing on ensuring these NPs ’ safety and efficacy in the intricate milieu of the human body. The unique electronic and magnetic properties of TbNPs, which make them attractive for various applications, also raise questions regarding their potential adverse effects on living organisms .…”
Section: Potential Challenges Of Tbnps In Biomedical Applicationsmentioning
confidence: 99%
“…Moreover, the iodinated contrast agents can also induce hyperthyroidism and contrastrelated nephropathy. 37,132 Therefore, recent investigations have suggested that TbNPs can be further utilized for bioimaging applications to detect biological substances or various disease biomarkers.…”
Section: Terbium-based Nps (Tbnps) For Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there remains a vast range of opportunities for further exploration. Lanthanides capable of operating as T 2 contrast agents, such as Tb, are coming under increasing scrutiny, 75–78 since T 2 contrast agents increase rather than decrease their efficiencies with increasing magnetic field strength. 79 As such, experimenting with Tb EMFs 80,81 could be a promising new avenue for expanding the state of the art in EMF-based MRI contrast agents.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%